Correlation Between Decreased CSF α-Synuclein and Aβ(1-42) in Parkinson Disease - Buddhala, Chandana (Neurobiol Aging, 2014)
Accumulation of misfolded α-synuclein (α-syn) protein in Lewy bodies and neurites is the cardinal pathologic feature of Parkinson disease (PD), but abnormal deposition of other proteins may also play a role. Cerebrospinal fluid (CSF) levels of proteins known to accumulate in PD may provide insight into disease-associated changes in protein metabolism and their relationship to disease progression. We measured CSF α-syn, Aβ(1-42) and tau from seventy-seven non-demented PD and thirty control participants. CSF α-syn and Aβ(1-42) were significantly lower in PD compared to controls. In contrast to increased CSF tau in Alzheimer disease, CSF tau did not significantly differ between PD and controls. CSF protein levels did not significantly correlate with ratings of motor function or performance on neuropsychological testing. As expected, CSF Aβ(1-42) inversely correlated with [(11)C]-Pittsburgh Compound B (PiB) mean cortical binding potential, with PiB(+) PD participants having lower CSF Aβ(1-42) compared to PiB(−) PD participants. Furthermore, CSF α-syn positively correlated with Aβ(1-42) in PD participants but not in controls, suggesting a pathophysiologic connection between the metabolisms of these proteins in PD.